Comparative Knowledge Level of the Organic and Conventional FarmersRegarding Organic Farming Practices in Jaipur, District of Rajasthan (Indian Journal of Extension Education, 2011)
Organic farming is one of the several approaches to sustainable agriculture, which is a necessity in today’s unstable and degrading environment. The present study was conducted in the 6 selected villages of purposely selected Govindgarh Panchayat Samiti of Jaipur district. From these villages 50 organic and 50 conventional farmers were selected by simple random sampling technique for the study purpose by proportional allocation method. It was found that majority of the organic farmers and half of the conventional farmers had medium level of knowledge about organic farming. There was a significant difference between the organic and conventional farmers in their knowledge levels about organic farming practices. It was also found that the organic farmers had highest knowledge regarding general information about compost, whereas the conventional farmers had highest knowledge about organic weed management. The organic farmers had significantly higher knowledge as compared to conventional farmers regarding general information about compost, organic weed management, biofertilizer, NADEP compost, trichocards, vermicompost and HaNPV. It was further found that in case of organic weed management both the organic and conventional farmers had highest knowledge about “Knowledge about losses caused by weeds”. The organic and conventional farmers had lowest knowledge about “Natural substances or plant extract which can control weeds”.